ECHOCARDIOGRAPHIC EVALUATION AND CLINICAL PROFILE OF DILATED CARDIOMYOPATHY: A CROSS-SECTIONAL OBSERVATIONAL STUDY IN A TERTIARY CARE TEACHING HOSPITAL (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Dilated cardiomyopathy (DCM) is a major cause of heart failure, arrhythmias, and sudden cardiac death worldwide. It is characterized by ventricular dilatation and impaired systolic function, leading to progressive cardiac dysfunction and significant morbidity and mortality. Echocardiography plays a vital role in the diagnosis and evaluation of DCM. The present study aimed to assess the echocardiographic findings and clinical profile of patients with dilated cardiomyopathy in a tertiary care teaching hospital. Methodology: A cross-sectional observational study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from December 2025 to May 2026. A total of 69 patients diagnosed with DCM based on clinical and echocardiographic criteria were included. Detailed history, physical examination, laboratory investigations, ECG, chest X-ray, and echocardiography were performed. Echocardiographic parameters including ejection fraction, left ventricular dimensions, and chamber dilatation were assessed. Results: The majority of patients were males (71%) and belonged to the 51–60 years age group (33.3%). Dyspnea was the most common symptom (76.8%), while raised jugular venous pressure was the most common clinical sign (72.5%). Ischemic heart disease was the leading etiology (30.4%), and hypertension was the most prevalent risk factor (58%). Conclusion: Dilated cardiomyopathy predominantly affects middle-aged males and commonly presents with features of congestive heart failure. Echocardiography remains an essential diagnostic tool for early identification and assessment of cardiac dysfunction in DCM.